Genome-Wide Single Nucleotide Polymorphisms are Robust in Resolving Fine-Scale Population Genetic Structure of the Small Brown Planthopper, Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) - Liu, Yan; Chen, Lei; Duan, Xing-Zhi; Zhao, Dian-Shu; Sun, Jing-Tao; Hong, Xiao-Yue (Journal of economic entomology, 2019)
Deciphering genetic structure and inferring migration routes of insects with high migratory ability have been challenging, due to weak genetic differentiation and limited resolution offered by traditional genotyping methods. Here, we tested the ability of double digest restriction-site associated DNA sequencing (ddRADseq)-based single nucleotide polymorphisms (SNPs) in revealing the population structure relative to 13 microsatellite markers by using four small brown planthopper populations as subjects. Using ddRADseq, we identified 230,000 RAD loci and 5,535 SNP sites, which were present in at least 80% of individuals across the four populations with a minimum sequencing depth of 10. Our results show that this large SNP panel is more powerful than traditional microsatellite markers in revealing fine-scale population structure among the small brown planthopper populations. In contrast to the mixed population structure suggested by microsatellites, discriminant analysis of principal components (DAPC) of the SNP dataset clearly separated the individuals into four geographic populations. Our results also suggest the DAPC analysis is more powerful than the principal component analysis (PCA) in resolving population genetic structure of high migratory taxa, probably due to the advantages of DAPC in using more genetic variation and the discriminant analysis function. Together, these results point to ddRADseq being a promising approach for population genetic and migration studies of small brown planthopper.